Assessing and explaining the relative efficiency of local government : evidence for portuguese municipalities - Afonso, António (2010)
In this paper we measure the relative efficiency of Portuguese local municipalities in a non-parametric framework approach using Data Envelopment Analysis. As an output measure we compute a composite local government output indicator of municipal performance. This allows assessing the extent of municipal spending that seems to be "wasted" relative to the "best-practice" frontier. Our results suggest that most municipalities could achieve, on average, the same level of output using fewer resources, improving performance without necessarily increasing municipal spending. Inefficiency scores are afterwards explained by means of a Tobit analysis with a set of relevant explanatory variables playing the role of non-discretionary inputs.